Strategi Komunikasi Pemberdayaan Masyarakat pada Perguruan Tinggi Islam - Yanti, Fitri; Amaliah, Eni (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2021)
This article discusses communication strategies for community empowerment carried out by universities. In an effort to achieve optimal targets, the role of effective communication is very pivotal. In this case, the right empowerment communication strategy is to place communicators as motivators, dynamists, innovators, and facilitators for social change. In this regard, students, lecturers, or companion teams as communicators must be on a par with the community. It means that communicator and audience, expert and user, and sender and receiver interchange roles in a mutually beneficial two-way interaction through which qualified social empowerment can be reached. The communicator functions as a driving force for the community to be able to realise their potential independently in order to become more empowered. This communication strategy is appropriate for the bottom-up intervention model of community empowerment; self-help and togetherness model, integrative-interconnected model, and asset based community-driven development.